Perlindungan Hukum Konsumen Air Minum Isi Ulang Pada Masyarakat Umum - Dwi Atmoko; Noviriska (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
The obstacle for consumers of refill drinking water to obtain legal protection is the low level of legal awareness for refill drinking water business actors regarding the obligation of business actors to provide correct and honest information regarding the conditions and guarantees regarding the refill drinking water they sell. Apart from that, another obstacle for consumers is that consumers do not know about the rights they have and consumers do not know where to complain and demand responsibility for the losses they experience, which is why many consumers do not get legal protection. Consumer rights are related to consumption. Drinking water refills are not working well. Refill drinking water depots do not provide information to consumers about the condition of refill drinking water, namely information about hygiene, valid registration marks, laboratory inspection results regarding the quality of refill drinking water. Business actors have violated the UUPK regarding consumer rights by not providing clear, honest and correct information to consumers. Business actors have a tendency to